Bertrand and price-taking equilibria in markets with product differentiation - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2008)
In this paper we show that a homogeneous-product market with multiple Bertrand equilibria becomes a market with a single Bertrand equilibrium when we introduce a small degree of product differentiation. When differentiation tends to zero, that Bertrand equilibrium converges to the unique price-taking equilibrium of the homogeneous-product market, which is in turn one of the multiple Bertrand equilibria for that market.
Keywords: D43; L13; 330; Bertrand equilibrium; price-taking equilibrium; product differentiation; Oligopol; Produktdifferenzierung; Theorie